2010
DOI: 10.1016/j.beproc.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Alloparenting experience affects future parental behavior and reproductive success in prairie voles (Microtus ochrogaster)

Abstract: Various hypotheses have been proposed to explain the function of alloparental behavior in cooperatively breeding species. We examined whether alloparental experience as juveniles enhanced later parental care and reproductive success in the prairie vole (Microtus ochrogaster), a cooperatively breeding rodent. Juveniles cared for one litter of siblings (1EX), two litters of siblings (2EX) or no siblings (0EX). As adults, these individuals were mated to other 0EX, 1EX or 2EX voles, yielding seven different pair c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Alloparental behavior decreases with age in females but not in males, young female voles (21–30 days) acted more parentally toward pups than older females, particularly those older than 45 days (age close to dispersal) (Lonstein and De Vries 2001; Stone et al 2010; Ophir, Wolff, and Phelps 2008). …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Alloparental behavior decreases with age in females but not in males, young female voles (21–30 days) acted more parentally toward pups than older females, particularly those older than 45 days (age close to dispersal) (Lonstein and De Vries 2001; Stone et al 2010; Ophir, Wolff, and Phelps 2008). …”
Section: Methodsmentioning
confidence: 98%
“…Field studies on the social organization of natural prairie vole populations have revealed that approximately 70% of male and 75% of young female prairie voles remain in the natal nest until death as non-breeding alloparents, sacrificing their reproductive opportunities (Getz, Hofmann, and Carter 1987; McGuire et al 1993; Stone et al 2010). These animals are defined as philopatric.…”
Section: Introductionmentioning
confidence: 99%
“…Stone and colleagues (Stone et al, 2010) paired male and female prairie voles with varying levels of alloparenting experience, and looked at offspring outcomes. Offspring of parents that had two litters of alloparental experience (either through two litters of experience for one parent, or one litter of experience for each parent) developed faster and displayed more male alloparenting themselves.…”
Section: Effects Of Male Parenting On Offspringmentioning
confidence: 99%
“…Various mammalian species that participate in cooperative breeding perform behaviors that range from feeding and allo-suckling to carrying pups (Russell, 2004). Other studies have previously observed alloparenting behaviors specifically in voles, such as huddling, pseudohuddling, time in/out of the nest, licking and sniffing, grooming, and retrieving pups (Stone et al, 2010, Keebaugh and Young, 2011). In addition to these behaviors towards siblings, carrying and side-by-side contact with unrelated pups have been observed in alloparenting tests (Roberts et al, 1996, Kirkpatrick and Kakoyannis, 2004).…”
mentioning
confidence: 94%